Controllable synthesis and defect-dependent photoluminescence properties of In2O3 nanostructures prepared by PVD. (10th May 2017) - Jin, Changqing; Wei, Yongxing; Peterson, George; Zhu, Kexin; Jian, Zengyun
Abstract: In2 O3 nanostructures were successfully synthesized via physical vapor deposition (PVD). It was found that the morphology of nanostuctures could be controlled by manipulation of the synthesis temperature, growth time, use of a Au-catalyst, selection of substrate material, and vapor pressure. A higher synthesis temperature is more favorable for the formation of 1D nanostructures. An increased growth time increased the width and length of the 1D nanostructures. Through the use of a Au-catalyst coated Si (1 0 0) substrate, we were able to preferentially synthesize (1 0 0) In2 O3 nanostructures, even at lower growth temperatures. This research shows that a Au-catalyst is necessary for the formation of one-dimensional (1D) In2 O3 nanostructures. Three dimensional (3D) octahedral nanoparticles are resultant from a Au-free Si (1 0 0) substrate. Al2 O3 (1 0 0) substrates were found to be energetically favorable for the synthesis of nanofilms, not 1D nanostructures, regardless of the presence of Au-catalyst. The photoluminescence curves indicate that the defect related luminescence is not a function of morphology, but rather the ratio of the partial vapor pressures of the constituent elements (In and O), which were controlled by the growth pressure.